The Spatial Construction of Rural Identity and the Protagonist’s Journey in Rakshadhikari Baiju Oppu: A Critical Analysis of Countryside Representation in Malayalam Cinema - Krishna, K. Anaswara; Nair, Shemin Balachandran (Journal of Neonatal Surgery, 2025)
This study examines the connection between Byju, the main character, and the rural area in Rakshadhikari Byju Oppu (2017), a Malayalam movie that deftly incorporates the rural location into its story. The study looks at how Byju's identity, emotional journey, and personal development are shaped by the rural area, which serves as both a physical backdrop and an active actor. The study examines how the protagonist's adherence to tradition, community, and simplicity is reflected in the countryside using Yi-Fu Tuan's spatial theory and cinematic approaches. A key component of Byju's character development is the examination of his enduring ties to his community and the land surrounding him.Analysis of the film's lighting, composition, and framing strategies reveals how the rural location is portrayed visually and how it supports the concepts of identification, belonging, and nostalgia. The study also explores the symbolism of rural areas as a place of solace and change, emphasizing the protagonist's inner turmoil and development. This study adds to our knowledge of how the protagonist's journey is portrayed in rural areas of Malayalam cinema, providing insights into the larger issues of custom, community, and personal development.